Humility challenges and facilitating factors among religious leaders: A qualitative study - Ruffing, Elizabeth G. (Journal of spirituality in mental health, 2020)
Previous research suggests that humility is important for religious leaders' mental health and for the health of the communities they lead. There is evidence, however, that humility is particularly difficult for some leaders, and numerous dynamics within the role of religious leadership may run counter to humility. This qualitative study asked 273 diverse religious leaders to identify factors within their roles that challenged and facilitated humility for them. Thematic analysis of the responses revealed ways that religious leaders can cultivate humility within and despite complex pressures against it. Practical implications for the care and support of religious leaders are discussed.